2008
DOI: 10.1177/112972980800900402
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous Fistulae vs. Arteriovenous Grafts: A Retrospective Review of 1,700 Consecutive Vascular access Cases

Abstract: AVF and grafts are both useful in providing VA for patients requiring hemodialysis. Our data shows that grafts are equivalent in long-term patency. Therefore, it is apparent in those patients who are not candidates for an AV fistula; an AV graft for VA should be placed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
93
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(101 citation statements)
references
References 29 publications
8
93
0
Order By: Relevance
“…Because of the high prevalence of catheter and graft use in the United States, European and United States studies are difficult to compare. The negative effect of catheters and grafts on albumin levels as well as the incidence of infection, and thus concomitantly higher CRP and IL-6 levels, is well known (12,14,19,20). Interestingly, both the prevalence of catheter use and the decrease in albumin and BMI in the US HEMO study were comparable with CONTRAST (6).…”
Section: Discussionsupporting
confidence: 67%
“…Because of the high prevalence of catheter and graft use in the United States, European and United States studies are difficult to compare. The negative effect of catheters and grafts on albumin levels as well as the incidence of infection, and thus concomitantly higher CRP and IL-6 levels, is well known (12,14,19,20). Interestingly, both the prevalence of catheter use and the decrease in albumin and BMI in the US HEMO study were comparable with CONTRAST (6).…”
Section: Discussionsupporting
confidence: 67%
“…Infection and thrombosis rates were higher with AVG compared with AVF; however, access salvage after a thrombotic event was superior with AVG (25). Table 2 provides the outcome data from various studies that evaluated LE-AVG as permanent dialysis vascular access.…”
Section: Long-term Benefits Of Le-avgmentioning
confidence: 99%
“…Conduits have been compared in a number of studies but no substantial benefits between different types have been reported 4 . Above all, the function and duration in terms of the emergence of stenotic and thrombotic complications have been monitored [13][14][15][16] . These complications are essentially reparable.…”
Section: Introductionmentioning
confidence: 99%
“…The lowest risk of infectious complications is in patients with native arteriovenous fistula, where the incidence is from 2 to 3% (ref. 13,29,32 ). In patients with arteriovenous graft the incidence of infection is from 11 to 35% (ref.…”
Section: Introductionmentioning
confidence: 99%